One-pot relay catalysis: divergent synthesis of furo[3, 4-b]indoles and cyclopenta[b]indoles from 3-(2-aminophenyl)-1, 4-enynols. Issue 24 (3rd March 2016) - Manisha,; Dhiman, Seema; Mathew, Jopaul; Ramasastry, S. S. V.
Abstract : Described herein a divergent strategy for the synthesis of furo[3, 4- b ]indoles via a sequential Ag(i )/Bi(iii )/Pd(ii ) catalysis and cyclopenta[ b ]indoles via a one-pot Ag(i )/Brønsted acid relay catalysis, starting from the easily accessible 3-(2 aminophenyl)-4-pentenyn-3-ols. Abstract : Described herein is an efficient divergent strategy for the synthesis of furo[3, 4- b ]indoles via a sequential Ag(i )/Bi(iii )/Pd(ii ) catalysis and cyclopenta[ b ]indoles via a one-pot Ag(i )/Brønsted acid relay catalysis from 3-(2-aminophenyl)-4-pentenyn-3-ols, accessible in three simple steps from 2-aminobenzaldehydes.